Collision-Detecting Device for Omnidirectional Electric Wheelchair. (29th November 2013) - Ishida, Shuichi; Miyamoto, Hiroyuki
Abstract : An electric wheelchair is the device to support the self-movement of the elderly and people with physical disabilities. In this paper, a prototype design of an electric wheelchair with a high level of mobility and safety is presented. The electric wheelchair has a high level of mobility by employing an omnidirectional mechanism. Large numbers of mechanisms have been developed to realize omnidirectional motion. However, they have various drawbacks such as a complicated mechanism and difficulty of employment for practical use. Although the ball wheel drive mechanism is simple, it realizes stable motion when negotiating a step, gap, or slope. The high level of mobility enhances the freedom of users while increasing the risk of collision with obstacles or walls. To prevent collisions with obstacles, some electric wheelchairs are equipped with infrared sensors, ultrasonic sensors, laser range finders, or machine vision. However, since these devices are expensive, it will be difficult for them to be widely used with electric wheelchairs. We have developed a prototype design of collision-detecting device with inexpensive sensors. This device detects the occurrence of collisions and can calculate the direction of the colliding object. A prototype has been developed to perform motion experiments and verify the accuracy of the device. The results of experiments are also presented in this paper.